Identifying genetic predictors of depression risk: 5-HTTLPR and BDNF Val66Met polymorphisms are associated with rumination and co-rumination in adolescents - Stone, Lindsey B.; McGeary, John E.; Palmer, Rohan H.; Gibb, Brandon E. (Frontiers in Genetics, 2013)
Background: Despite research supporting moderate heritability of depression, efforts to replicate candidate gene associations to depression have yielded inconsistent results. We tested whether Val66Met and 5-HTTLPR exhibit utility as genetic markers of depression risk, testing for replicable associations to cognitive and interpersonal endophenotypes of depression (rumination and co-rumination), and further exploring developmental and sex moderation. Method: In Study I, 228 youth (ages 8-14) of mothers with or without a history of MDD during the child’s lifetime were recruited from the community. Replication tests were carried out in Study II, a sample of 87 youth with similar recruitment. Results: In Study I, the Val66Met SNP was associated with rumination in adolescents, but not children, such that adolescents homozygous for the Val allele reported higher rumination levels. Further, a cumulative genetic score (Val66Val and 5-HTTLPR) predicted higher levels of co-rumination, specifically among adolescent girls. Both genetic associations maintained significance after covarying for current depressive symptomology, and the other endophenotype. Finally, both genetic associations exhibited similar effect sizes in Study II, although results did not reach statistical significance. Conclusions: Results replicate a previously reported association between the BDNF Val allele and rumination in adolescents, and provide preliminary support for a cumulative genetic score predictive of co-rumination in adolescent girls. The current study indicates that candidate genes may demonstrate utility as consistent genetic markers of depression risk when focused on specific phenotypes, and supports the need to explore potential differential effects of developmental stage and sex. However, given the small sample sizes and possibility of chance findings, these results should be interpreted with caution pending replication.